Pathways Linking Climate Change to Livestock Production and Consumption in Sub-Saharan Africa: A Protocol for a Systematic Review - Tareke, Amare Abera; Zerfu, Taddese Alemu; Hailesilassie, Wondimu Tadiwos; Bosire, Caroline; Mukherji, Aditi (CGIAR System Organization, 2025)
The sub-Saharan African (SSA) region has a large livestock population but low productivity and animal source foods consumption which contributed to nutritional problems. Climate change further reduces productivity, impacting the livelihoods of the rural poor who largely rely on livestock. The agri-food system of SSA is characterized by small holder traditional family farms, poor technological uptake, poor infrastructure, poor veterinary services, and weak adaptability to climate effects. Owing to the unique challenges in climate change and agri-food system interface in SSA, contextualized evidence is very important to design interventions. We aimed to synthesize evidence on the pathways linking climate to livestock production and animal source food consumption in SSA context. Understanding the pathways linking climate change to livestock production and consumption in SSA is essential for formulating strategies that enhance food security, improve nutrition, and support rural livelihoods while mitigating and adapting to the impacts of climate change.